Management of middle mesial canal in mandibular second molar - J V Karunakaran; R Shobana; Mohan Kumar; Senthil Kumar; Sunil Mankar (Wolters Kluwer Medknow Publications, 2012)
The primary objective of endodontic therapy is to achieve a three-dimensional obturation of the root canal space after adequate preparation of the canal space to remove the tissue debris, microorganisms, and their byproducts. Anatomical variations have frequently been encountered in endodontic practice and have to be adequately managed by the clinician. Missed roots and canals are a major reason for failure of therapy. Technological advances have given the clinician ample opportunity to identify and treat these aberrations successfully. The present report describes a left mandibular second permanent molar requiring root canal treatment, found to have three separate canals in the mesial root. This case demonstrates a rare anatomical configuration and emphasizes the need for the clinician to be aware of and look out for such variations and use adequate diagnostic methodologies prior to and during therapy to detect such variations. The possibility of additional canals, whenever in doubt, should be explored with the assistance of technologies such as those of magnification and illumination and various diagnostic aids. Operator experience has also shown to be a key factor in negotiation and management of these aberrant canal configurations.